DEVELOPING INTERACTIVE MULTIMEDIA TO TEACH READING NARRATIVE TEXT USING ADOBE FLASH CS6 - Oktaviyani, Sherli; Regina, Regina; Wardah, Wardah (Universitas Tanjungpura, 2022)
This research aims to find out the target needs, learning needs and developed theappropriate reading interactive multimedia for the tenth-grade students of MAN2 Pontianak. This is a Research and Development (RD) using ADDIEprocedures. ADDIE stands for Analysis, Design, Develop, Implement, andEvaluate. The subjects of this research were the English teacher and the tenth-grade students of MAN 2 Pontianak. The data were collected through interviews,questionnaires, and expert judgments. The researcher used Adobe Flash CS6 todevelop interactive multimedia. The result of the needs analysis showed that thestudents needed interesting materials, fun activities, and animation videos tosupport their learning English, especially in reading skills. Therefore, this studydeveloped the topic of narrative text, which was implemented in interactivemultimedia. This interactive multimedia consists of materials of the narrativetext, narrative story, animation videos with subtitles, and quiz with four activities.This interactive multimedia focused on learning the correct pronunciation,vocabulary, grammar (past tense), and the text types of narrative text. Based onthe result both from the teacher and the multimedia expert, it said that theinteractive multimedia quality belongs to the